A Survivor of Neonatal Intestinal Mucormycosis - Sathe, Pragati Aditya (J Clin Diagn Res, 2015)
Gastrointestinal mucormycosis (GIM) is a rare opportunistic fungal infection. One third of all patients are children and of these, 50% are infants. The most common clinical mimic is necrotizing enterocolitis (NEC). It has to be differentiated from this entity as the treatment is entirely different. High index of suspicion by the clinicians and the pathologists aids in early diagnosis and immediate treatment. If untreated, it has a frequent fatal outcome. Very few survivors of GIM are found in literature. We report a rare case of a surviving neonate of GIM.